West Antarctica's sensitivity to natural and human‐forced climate change over the Holocene. (14th December 2012) - Mayewski, P. A.; Maasch, K. A.; Dixon, D.; Sneed, S. B.; Oglesby, R.; Korotkikh, E.; Potocki, M.; Grigholm, B.; Kreutz, K.; Kurbatov, A. V.; Spaulding, N.; Stager, J. C.; et al.
Abstract: The location and intensity of the austral westerlies strongly influence southern hemisphere precipitation and heat transport with consequences for human society and ecosystems. With future warming, global climate models project increased aridity in southern mid‐latitudes related to continued poleward contraction of the austral westerlies. We utilize Antarctic ice cores to investigate past and to set the stage for the prediction of future behaviour of the westerlies. We show that Holocene West Antarctic ice core reconstructions of atmospheric circulation sensitively record naturally forced progressive as well as abrupt changes. We also show that recent poleward migration of the westerlies coincident with increased emission of greenhouse gases and the Antarctic ozone hole has led to unprecedented penetration, compared with >100, 000 years ago, of air masses bringing warmth, extra‐Antarctic source dust and anthropogenic pollutants into West Antarctica. Copyright © 2012 John Wiley & Sons, Ltd.